Revitalization of Dompu Traditional Industry as a Pillar of Creative Economy Based on Local Culture - M. Ahleyani; Andre Kurniawan Pratama; Ranjiv A. A Sihombing; Irma Widi Astuti; Althaf Fikar Harik Nusantara (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study aims to analyse the potential for revitalising traditional industries in Dompu Regency, West Nusa Tenggara, as a pillar of creative economic development based on the local culture